The Influence Of Price And Service Quality On Customer Satisfaction Of Bus 27 Trans Route Malang – Bandung Through Purchasing Decisions - Ghaluh Iedmu’ammar Iedmu’ammar; Putu Nina Madiawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Transportation plays an important role in facilitating human mobility in carrying out various activities such as work, education, tourism and traveling. The current situation has given rise to increasingly fierce competition between various modes of transportation, including air, sea and land. This research aims to determine the direct influence of price and service quality on purchasing decisions and to test the indirect influence of price and service quality on customer satisfaction through purchasing decisions. The research method in this research is descriptive and quantitative. The sampling technique used in this research is a non-probability sampling technique with a focus on purposive sampling, and using the Cochran formula to obtain a sample of 100 respondents in the study. The analytical method used in this research is structural equation modeling-partial least squares (SEM-PLS). Based on the results of hypothesis testing, it shows that price has a direct influence on purchasing decisions, service quality has a direct influence on purchasing decisions, purchasing decisions have a direct influence on customer satisfaction, and price has an indirect influence on customer satisfaction through purchasing decisions and service quality has an indirect influence on customer satisfaction. through purchasing decisions.